Makna Tadabbur Menurut Mufassir Klasik dan Modern: Sebuah Pembacaan Historis - Abu Sufyan (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Meaning of Tadabbur According to Classical and Modern Mufassir: A Historical ReadingThis paper aims to explore the meaning of tadabbur from the classical to the contemporary era. Departing from the lack of popularity of tadabbur terminology in their literature, this study shows that the meaning of tadabbur tends to be understood textually by classical commentators, as well as contextual meaning by modern commentators. By using a language approach and the history of interpretation, this paper does not focus on tadabbur as the practice of reading the Qur’an by certain groups, but on a conceptual study that is aligned with “tafsir” and “ta’wil”. This search was carried out using a literature study with a comparative-analytic method, which tried to show historical evidence of interpretation and bring it into the context of tadabbur in QS. Āl ‘Imrān: 7 based on the meaning of classical and modern commentators. This study finds that classical commentators understand tadabbur as a practical term that is at the level of reading the Qur’an (qira’ah). For them, this term represents certain theological meanings, including tilāwah, tabaṣṣur, and istinbāṭ. Meanwhile, in the view of the modernist group, tadabbur is understood as a methodological term that is at the level of interpretation (tafsir tadabburi). This is confirmed again by the urge to do ijtihad and leave taqlid